2015
DOI: 10.1051/0004-6361/201526596
|View full text |Cite
|
Sign up to set email alerts
|

Restarting radio activity and dust emission in radio-loud broad absorption line quasars

Abstract: Context. Broad absorption line quasars (BAL QSOs) are objects that show absorption from relativistic outflows that have velocities up to 0.2c. In about 15% of quasars, these manifest as absorption troughs on the blue side of UV emission lines, such as C  and Mg .The launching mechanism and duration of these outflows is not clear yet. Aims. In this work, we complement the information collected in the cm band for our previously presented sample of radio loud BAL QSOs (25 objects with redshifts 1.7 < z < 3.6)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The radio luminosities at low and high frequencies are correlated with each other, which is consistent with both processes being driven by the same AGN. One possibility is that these AGN could be undergoing rapid bursts of activity, and the low-frequency observations trace the steep-spectrum remnants of previous outbursts, while the high frequency observations trace the current AGN activity, as suggested by Bruni et al (2015) and .…”
Section: Where Does Balqso Radio Emission Come From?mentioning
confidence: 96%
“…The radio luminosities at low and high frequencies are correlated with each other, which is consistent with both processes being driven by the same AGN. One possibility is that these AGN could be undergoing rapid bursts of activity, and the low-frequency observations trace the steep-spectrum remnants of previous outbursts, while the high frequency observations trace the current AGN activity, as suggested by Bruni et al (2015) and .…”
Section: Where Does Balqso Radio Emission Come From?mentioning
confidence: 96%
“…APM 08279+5255 does have radio emission and its luminosity does put it into the FRII category so it could indeed have a misaligned, highly powerful radio jet, but some (perhaps all) of this radio emission is powered by the strong star formation (Riechers et al 2009). The high resolution radio images show no sign of a double radio structure (Riechers et al 2009), but these could be suppressed by being on scales which are outside of the lensing magnificantion and/or the source could be young, like the GHz peaked AGN (Bruni et al 2015).…”
Section: Broadband Sed and Quasar Parametersmentioning
confidence: 99%
“…The latest results from our m-and mm-band campaign (Bruni et al 2015), present some new highlights on the dust abundance, found to be even lower than in normal QSOs. This could suggest a lower star formation rate, possibly inhibited as a feedback effect of the relativistic BAL-…”
Section: Discussionmentioning
confidence: 72%